2021
DOI: 10.1002/ejp.1746
|View full text |Cite
|
Sign up to set email alerts
|

The effect of experimental pain on the excitability of the corticospinal tract in humans: A systematic review and meta‐analysis

Abstract: Background and objective Pain influences motor control. Previous reviews observed that pain reduces the excitability of corticospinal projections to muscles tested with transcranial magnetic stimulation. However, the independent effect of the type of pain models (tonic, phasic), pain location and tissues targeted (e.g. muscle, skin) remains unexplored. The objective of this review was to determine the influence of experimental pain and of different methodological factors on the corticospinal excitability. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 79 publications
0
33
1
Order By: Relevance
“…Motor performance is impaired in FM patients 31 , and motor cortex metabolism basically reduced when strictly related to active movement. Movement observation provokes motor networks activations and modulation, which suggests cortical adaptation mechanisms able to restart a virtuous phase of beneficial interaction with pain-related circuits 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Motor performance is impaired in FM patients 31 , and motor cortex metabolism basically reduced when strictly related to active movement. Movement observation provokes motor networks activations and modulation, which suggests cortical adaptation mechanisms able to restart a virtuous phase of beneficial interaction with pain-related circuits 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Third, pain can trigger alterations in the construct of learning, which in turn can lead to neuroplastic changes in the cortex; however, we only reported data regarding behavioral response in the presence of experimental pain models, and excluded studies that focused only on neural plasticity. While a recent systematic ( Rohel et al, 2021 ) examined the effects of pain on corticospinal excitability, there is still an open question regarding the general effects of pain on neural plasticity induced during motor learning. Finally, the heterogenous nature of the included studies did not allow us to perform a meta-analysis, and therefore a narrative synthesis of the included studies was done instead.…”
Section: Discussionmentioning
confidence: 99%
“…It has to be noted nevertheless that chronic pain does not necessarily have the same effect as acute pain. While previous studies of systemic review and meta-analysis showed reduced corticospinal excitability in the patients with experimental acute pain [ 28 , 29 ], no consistence pattern on TMS variables was observed for the chronic pain conditions [ 30 ]. In addition, our participants with SIS may change their movement patterns to avoid moving their affected shoulder due to pain.…”
Section: Discussionmentioning
confidence: 86%